If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6z+6=66
We move all terms to the left:
6z+6-(66)=0
We add all the numbers together, and all the variables
6z-60=0
We move all terms containing z to the left, all other terms to the right
6z=60
z=60/6
z=10
| 6(g-85)=78 | | 60x=9,600 | | 7(q+2)=28 | | -20z8+7=9 | | X=-1.5x+30 | | 26x+19=48x+12 | | 67=y-13 | | 10000=7000(2)^4t | | 11x4/5-1=4/5+1 | | 2.4x8= | | 3n6=19 | | 68=y-281 | | b+46=3b | | 13.8+k=100 | | X+2x+11=65 | | 12=6+-3u | | n+.08=10 | | 3-2w=-5 | | 3x+7=2x-3=36 | | -8+8b=7(2b+4) | | p-41=48 | | 8a+5a=2 | | p+52=14p | | 2.8+k=6.1 | | X-1=16+4x | | a+46=2a | | 4x+21=7x+3 | | 2/3a+2=4 | | 4d–35=-3 | | -5/3r+17=27 | | -11m=682 | | 4x-6=2x+39 |